so start with y = -x^2 + 5x + 7 then complete the square: = -(x^2 -5x -7) = -(x^2 -5x + 4/25 - 7 -4/25) = -( (x-2/5)(x-2/5) -7 -4/25) = -(x-2/5)^2 -(7 4/25)
20x+7=5x+10 15x=3 3/15=.2 x=.2
9x + 7 = 5x + 35Subtract 5x from each side of the equation:4x + 7 = 35Subtract 7 from each side:4x = 28Divide each side by 4:x = 7
2x + 5x + 25 = 17x + 25 = 1Subtract 25 from each side of the equation:7x = -24Divide each side by 7:x = -24/7That's the only answer there is.
y=5x+2 if y equals -4
It is: 8-5x simplified
35x^2 + 77x + 42 Improved answer: 5x+67x+7 When simplified = 72x+7
The given expression can be simplified to: 2x-2
It is: y = -5x+7
It is an algebraic expression that can be simplified to: 5x+9y+5
10x+7 = 5x+32 10x-5x = 32-7 5x = 25 x = 5
If: 5x = 4x+7 Then: 5x-4x = 7 And: x = 7
If: 10x+7 = 5x+22 Then: 10x-5x = 22-7 And: 5x = 15 So: x = 3
5x+3x-6x+4x+2x-x+10 This expression can be simplified to: 7x+10 (7 being the coefficient of x)
5x - 3 + 2x + 7 = ?7x + 5 = ?
The expression to simplify is 4+6i+7 Answer: 6i + 11